Impact of phosphamidon on total protein, carbohydrate and lipid contents during the larval development of Sesarma brockii de Man - Kannupandi, T; Vijayakumar, G; Soundarapandian, P (Indian Journal of Fisheries, 2011)
Exposing the four zoeal and megalopal stage of the mangrove crab Searma borckiito different concentrations of phosphamidon, the larval survivability and thebiochemical constituents such as protein, carbohydrate and lipid were studied. Inall three test concentrations (0.025,1.108 and 1.600 ng/1) studied, a reduction insurvival rate, prolonged intermoult duration and decrease of total protein, carbohydrateand lipid contents was observed. The result was subjected to 'F' test andmultiple range test to know their statistical significance